Proliferation of myogenic stem cells in human skeletal muscle in response to low‐load resistance training with blood flow restriction - Nielsen, Jakob Lindberg; Aagaard, Per; Bech, Rune Dueholm; Nygaard, Tobias; Hvid, Lars Grøndahl; Wernbom, Mathias; Suetta, Charlotte; Frandsen, Ulrik (The Journal of physiology, 2012)
Key points In the last decade muscle training performed using a combination of low external loads and partial restriction of blood flow to the exercising limb has gained increasing interest, since it leads to significant gains in muscle strength and muscle mass. The cellular mechanisms responsible for the muscular adaptations induced by this training paradigm are not fully understood. This study shows that 3 weeks of high‐frequency, low‐intensity muscle exercise with partial blood flow restriction induces increases in maximal muscle strength accompanied by highly marked gains in muscle fibre size. Furthermore, the results indicate that these muscular adaptations rely on a considerable upregulation in myogenic satellite cells number, resulting in nuclear addition to the exercised myofibres. The results contribute to a better understanding of the physiological mechanisms underlying the gain in muscle strength and muscle mass observed with blood flow restricted low‐intensity resistance exercise. Low‐load resistance training with blood flow restriction has been shown to elicit substantial increases in muscle mass and muscle strength; however, the effect on myogenic stem cells (MSCs) and myonuclei number remains unexplored. Ten male subjects (22.8 ± 2.3 years) performed four sets of knee extensor exercise (20% 1RM) to concentric failure during blood flow restriction (BFR) of the proximal thigh (100 mmHg), while eight work‐matched controls (21.9 ± 3.0 years) trained without BFR (control, CON). Twenty‐three training sessions were performed within 19 days. Maximal isometric knee extensor strength (MVC) was examined pre‐ and post‐training, while muscle biopsies were obtained at baseline (Pre), after 8 days intervention (Mid8) and 3 (Post3) and 10 days (Post10) post training to examine changes in myofibre area (MFA), MSC and myonuclei number. MVC increased by 7.1% (Post5) and 10.6% (Post12) (P < 0.001) with BFR training, while type I and II MFA increased by 38% (Mid8), 35–37% (Post3) and 31–32% (Post10) (P < 0.001). MSCs per myofibre increased with BFR training from 0.10 ± 0.01 (Pre) to 0.38 ± 0.02 (Mid8), 0.36 ± 0.04 (Post3) and 0.25 ± 0.02 (Post10) (P < 0.001). Likewise, myonuclei per myofibre increased from 2.49 ± 0.07 (Pre) to 3.30 ± 0.22 (Mid8), 3.20 ± 0.16 (Post3) and 3.11 ± 0.11 (Post10), (P < 0.01). Although MFA increased in CON at Mid8, it returned to baseline at Post3. No changes in MSC or myonuclei number were observed in CON. This study is the first to show that short‐term low‐load resistance exercise performed with partial blood flow restriction leads to marked proliferation of myogenic stem cells and resulting myonuclei addition in human skeletal muscle, which is accompanied by substantial myofibre hypertrophy.